Age differences in emotion perception in a multiple target setting: an eye-tracking study [dataset] - Mertens, Alica; Voß, Andreas; Spaniol, Julia; Hische, Amelie; Sauer, Nicole (Universität, 2019)
Research focusing on the association between age and emotion perception has revealed inconsistent findings, with some support for an age-related po...
Deposit date 2019-06-11
Gesehen am 19.06.2019
Keywords: Forschungsdaten; Datenbank